(untitled) (American Journal of Engineering , Mechanics and Architecture (2993-2637), 2023)
Recently, in a number of farms, ok-aryks have been replaced by flexible nylon pipelines with a hole for releasing water near each furrow. To lay and assemble them, they use a special device that is mounted on tractors. The use of nylon pipelines is promising, and even necessary in vineyards planted on slopes. This method is also important when irrigating saline lands with high groundwater levels, as it avoids the removal of salts to the soil surface. As a last resort, turf (chim) is laid at the beginning of irrigation furrows. Labor costs for infiltration irrigation of a vineyard along furrows using siphons are less than when irrigating with chim.